Scalability and stability in CO2 reduction via tomography-guided system design - O'Brien, Colin P.; McLaughlin, David; Böhm, Thomas; Xiao, Yurou Celine; Edwards, Jonathan P.; Gabardo, Christine M.; Bierling, Markus; Wicks, Joshua; Sedighian Rasouli, Armin; Abed, Jehad; Young, Daniel; Dinh, Cao Thang; et al. (Joule, 2024)
Electrocatalytic CO2 reduction offers a means to produce value-added multi-carbon products and mitigate CO2 emissions. However, the stability of CO2 electrolyzers for C2+ products has not exceeded 200 h—well below that of CO- and H2-producing electrolyzers—and the most stable systems employ low-conductivity substrates incompatible with scale. Current gas diffusion electrodes (GDEs) become filled with salt precipitate and electrolyte, which limits CO2 availability at the catalyst beyond 30 h. We develop a GDE architecture that is resistant to flooding and maintains stable performance for >400 h. Using a combination of focused ion beam scanning electron microscopy, micro-computed tomography, and a purpose-built array tomography technique, we determine that the enhanced stability is due to a percolating network of polytetrafluoroethylene in the microporous layer that retains hydrophobicity. We scale this approach in an 800 cm2 cell and an 8,000 cm2 stack and transfer >108 C, the largest reported CO2 electrolysis demonstration.
CRIS-Team Scopus Importer:2024-08-30
Keywords: cleantech; CO; CO; electrochemistry; gas diffusion electrode; renewable chemicals; renewable fuel; scalability; stability; tomographic reconstruction